Contributions of Financial Systems to Growth in OECD Countries - Leahy, Michael (OECD Economics Department Working Papers, 2001)
The recent period of sustained high growth in the United States has drawn attention to its financial system and the efficiency with which it seems to be able to channel funds to new productive investment projects, particularly in hi-tech industries. This study examines the role played by the financial systems in OECD countries and how they affect resource allocation and growth. It provides evidence suggesting that legal and regulatory framework conditions for financial systems, and particularly their enforcement and transparency, support innovation and investment in new enterprises. In addition, using dynamic panel regression techniques, the study finds significant relationships between investment and financial development, as measured by indicators of the scale of financial activity. Evidence is also found of significant relationships between financial development and growth - over and above the links via investment - indicating impacts via overall economic efficiency ...